American Breakfast - Mexican Dinner (Draft 4) - Daugharty, Janice (My University, 1990)
Daugharty, Janice. "American Breakfast - Mexican Dinner," n.d. Series 2: The Short Stories, 2, Box: 36; Box: 37; Box: 45. Janice Daugharty Papers, MS-22. Valdosta State University Archives and Special Collections. Box 37, Folder 1.
Daugharty, Janice. "American Breakfast - Mexican Dinner," n.d. 1 electronic record. 1 pdf document. 17 scans.
Keywords: Daugharty, Janice, 1944-; American literature--Women authors; Short stories